Relativização das regras de impenhorabilidade absoluta: considerações da doutrina e da jurisprudência com vistas à efetividade da tutela executiva. - Silva Neto, Pedro Luciano da (2015)
The procedural legislation provides mechanisms to give effect to the satisfaction of the debt, but also takes care to protect the heritage, with views to keep the minimum for his dignified survival. In this step, fit the assumptions of absolute and relative unseizability. Those are provided for in art. 649, of the Code of Civil Procedure, which will be the focus of this academic work. However, it’s important expatiate executive tutelage. In the first chapter, will be talked about its historical development. In the second chapter, will be studied the specific principles that guide the implementation process. In the next chapter, deals with the attachment and its legal aspects, and, in particular, the procedure for applying the right amount, from which it is inserted. The last chapter will examine the legal assumptions of absolute unseizability, according to the doctrinal and jurisprudential views.